Microbiome identification from ice ice disease infected Kappaphycus alvarezii using 16S rRNA gene sequence analysis and in silico docking studies against carrageenan degrading bacteria. (August 2020) - Riyaz, S.U. Mohammed; Prabhu, N. Srinivasa; Nalini, S.; Tejaswini, G.; Christy, H. Jemmy; Inbakandan, D.
Abstract: The seaweeds are taxonomically diverse group of marine plants found in intertidal and sub-tidal regions all over the world. Like other plants seaweeds are also affected by microbial pathogens it reduces the quality and market value of seaweeds. Kappaphycus alvarezii is a main source for carrageenan it gets affected by microbiome in unfavorable conditions which leads to the formation of white thalli disease namely called as Ice-ice disease, where the seaweed tissue become white and hard. In this study we have isolated eight different bacterial species from ice -ice diseased seaweed and identified using molecular analysis and established these species has key role to cause the disease by producing kappa carragenase enzyme which hydrolysis kappa carrageenan. Molecular docking has been extensively used to discover new targets for existing and natural bacterial compounds or enzymes. Molecular docking was employed as an effective approach to locate the potential binding site of macromolecular targets, encouraging interaction with GLN102, ARG151, TYR161, GLU163, ASP168, TRP194, ARG196, ARG260. The results suggest that molecular docking is an effective approach to locate and identify the target bacterial enzyme which has carragenan degrading activity. The present study evidently demonstrates the degrading of kappa-carragenan by kappa-carragenase enzyme from particular bacterial strain namely P.carragenovara .